Thankful Enough? Gratitude and Ingratitude in Politics - Rapior, Waldemar (Cambio. Rivista sulle Trasformazioni Sociali, 2026)
Robert van Krieken notes that Norbert Elias provides one of the most systematic sociological descriptions of the social and historical dynamics of various processes driving the pacification of hostility and the dismantling of antagonism. He states that Elias wrote about the emotions that drive such antagonism, including aggression, anger, embarrassment, fear, shame, happiness, sadness, hatred, repugnance and disgust, and alongside his concern with the ways in which antagonism in human relations has been pacified over time (van Krieken 2024: 22) Van Krieken lists a wide range of emotions, which surprisingly excludes gratitude. This article aims, among other things, to fill this gap. Gratitude is, in fact, as significant in the dialectical process of civilization/decivilization as national pride. We can consider gratitude a part of pacifying aggression, but also emerging antagonism. This article aims to analyze the dialectic of gratitude/ingratitude as political emotions; fill a gap in Eliasian sociology by including gratitude as a key emotional factor in the pacification and/or antagonization processes; show how gratitude serves to discipline international partners. Based on the example of US–Polish–Ukrainian relations in the aftermath of Russia’s full-scale invasion of Ukraine in 2022, this text demonstrates how the expression of and demand for gratitude connect to shaping the boundaries of international solidarity.